Exceeding Expectation and the Knotty Question of State Tourism Policy - Hunt, Kathryn (Maine Policy Review, 2003)
In the Margaret Chase Smith Essay, Kathryn Hunt reflects on Maine tourism policy, using as a springboard for discussion two recent events: the National Folk Festival held in Bangor and the Biathlon World Cup held at the Maine Winter Sports Center venue in Fort Kent.
Keywords: Maine tourism; Maine Winter Sports Center; National Folk Festival